The Powers of Mimesis: Simulation, Encounters, Comic Fascism - Lawtoo, Nidesh (Theory and event, 2019)
This essay establishes a first genealogical link between William E. Connolly's pluralist thought and a recent mimetic turn—or re-turn of mimesis—in critical theory. Crafting new connections between Connolly's diagnostics of affective contagion, crowd behavior, and aspirational fascism, on the one hand, and a Nietzschean diagnostic of the Dionysian powers of simulation, the mimetic unconscious, and the contagious intoxications it generates, on the other, the essay opens up new possibilities for encounters between new materialism, poststructuralism, and mimetic theory via the ancient view that humans are, for better and worse, imitative creatures—or Homo mimeticus. In the process, it align Connolly's insights into the powers of mimesis with a minor tradition in continental philosophy—from Nietzsche to Deleuze—and furthers a Janus-faced evaluation of satirical TV shows that fight contra (new) fascism at the level of the message, yet might further comic fascism at the level of the mass medium.